Study on Drivers’ Visual Load Features in Lighting Environments of Interior Zones of Extra-Long Tunnels over 10 km - Yuantao Zhou; Shiyong He; Xiaohu Li; Yingying Li; Guoping Du (Advances in Civil Engineering)
In extra-long road tunnels (>10 km), the interior zone accounts for 95% of the total tunnel length. Driving for an extended period in the interior zone of such a tunnel in a monotonous and dimly lit environment causes heavy visual loads for drivers and undermines the safe operation of tunnels and driving comfort. This study investigated the changing patterns of drivers’ visual loads while driving through road tunnels. In a real vehicle experiment, the pupil diameter, fixation duration, electroencephalogram power spectral density, standard deviation of normal to normal, and root mean square of successive differences were used as indicators of drivers’ visual loads. By comparing the differences in psychological and physiological parameters in tunnels of four different lengths, this study discovered the changing pattern of drivers’ visual loads in the interior zone of extra-long tunnels and merged multi-source information of various indicators based on the entropy evaluation model to obtain comprehensive visual load values for drivers. The experiment revealed that as the tunnel length increased, the changing patterns of the drivers’ visual load indicators diverged. In particular, the driver’s tension levels began to spike after 180s of driving. The comprehensive visual load values of drivers, combined with the change features of multiple indicators, provide a more accurate and complete assessment of visual loads. The analysis of drivers’ visual load features can provide a theoretical basis for measures to optimise the lighting environment of the interior zone of extra-long tunnels over 10 km.